Role of Service in Economic Growth (Trinity Journal of Management, IT & Media (TJMITM), 2015)
In India the services sector with an around 57 per cent contribu tion to the gross domestic product (GDP) has made rapid strides  in the last few years and emerged as the largest and fastest-grow ing sector of the economy. Besides being the dominant sector in  India’s GDP, it has also contributed substantially to foreign in vestment flows, exports, and employment. India’s services sec tor covers a wide variety of activities that have different features  and dimensions. The service sector comprises commercial banks,  insurance companies, non-banking financial companies, co-oper atives, pension funds, mutual funds and other smaller financial  entities. The financial sector in India is predominantly a banking  sector with commercial banks accounting for more than 60 per  cent of the total assets held by the financial system.
Keywords: Economic Growth; (GDP); non-banking financial companies; co-oper atives; insurance companies